Stereoselective Synthesis of Proline‐Derived Dipeptide Scaffolds (ProM‐3 and ProM‐7) Rigidified in a PPII Helix Conformation. Issue 13 (25th March 2014) - Reuter, Cédric; Kleczka, Margarethe; de Mazancourt, Sarah; Neudörfl, Jörg‐Martin; Kühne, Ronald; Schmalz, Hans‐Günther
Abstract: Following a peptide coupling/metathesis‐based strategy, the two diastereomeric scaffolds ProM‐3 and ProM‐7 were stereoselectively synthesized (as 9‐fluorenylmethoxycarbonyl derivatives), and their configuration was unambiguously proven by means of X‐ray crystallography. The required dehydroisoleucine building blocks were prepared by applying the enantioselective Kazmaier–Claisen rearrangement. The target compounds represent dipeptide analogs rigidified in a PPII helix conformation, which are of interest for the development of new proteomimetics that selectively bind to protein domains specialized in the recognition of ligands adopting a PPII helix secondary structure. Abstract : Starting from amino acid building blocks with an olefin side chain, the diastereomeric scaffolds ProM‐3 and ProM‐7 are synthesized through peptide coupling and ring‐closing metathesis. The conformationally defined dipeptide analogs are of interest as building blocks for the synthesis of modular PPII helix secondary structure mimetics as tailored inhibitors of protein–protein interactions.